Features of the seasonal dynamics of ambulance calls for patients with angina pectoris - V. A. Belyaeva (Сеченовский вестник, 2019)
Angina pectoris is a chronic disabling heart disease that leads to myocardial infarction and death without proper treatment. Aim - to study the dynamics of frequency of ambulance сalls for patients with stable angina in diﬀerent seasons of the year, depending on the current meteorological factors.Materials and methods. 1034 cases of calls of the emergency medical service in the city of Vladikavkaz to the patients with angina attack were analyzed. Based on the seasonal ranking of the ambulance frequency calls and the corresponding base of meteorological parameters, a correlation analysis of the relationship between these indicators was made. Results. It has been established that the seasonality factor inﬂuences the frequency of calls to the ambulance (2=9.12; KW-H=8.92). Correlations between the frequency of calls to the ambulance and meteorological factors are seasonally speciﬁc and vary with respect to annual coeﬃcients. The most signiﬁcant contribution to the increase in the incidence of angina attacks is made by the factors: average daily air temperature, inter - day variability of atmospheric pressure, relative humidity, cloudiness, pathogen indices of these factors, as well as a general index of weather pathogenicity.Conclusion. In winter, due to the negative impact of low temperatures and sharp variations in the whole complex of meteorological factors, the maximum number of ambulance calls to patients with angina is recorded. The most favorable period for patients suﬀering from angina pectoris is the summer season, during which emergency medical care is minimal.